A proposed conceptual model for examining acceptance of corporate massive open online courses (moocs): integrating social support and sense of belonging in technology acceptance model (TAM) - Buyut, Veronica Clement; Abdullah, Salfarina; Abdullah, Rusli; Atan, Rodziah (Insight Society, 2024)
MOOCs, or massive open online courses, have become increasingly popular in the last several years to offer employees online training and development opportunities. Traditional methods of training, such as in-house or external trainings, frequently provide several obstacles, including high prices, logistical complications, and time limits. MOOCs have leveled the playing field in online learning by making quality education available to everyone, especially working adults, allowing them to reskill and upskill their work abilities by offering scalable, flexible, and cost-effective alternatives to address issues encountered in traditional methods of training. Even though MOOCs have been the subject of extensive research in educational institutions, there has been relatively little investigation on the acceptance of MOOCs at the organizational level, particularly among employees. The main challenges with MOOCs are their low completion rates and high dropout rates. This research aims to fill a gap in the literature by providing a Corporate MOOCs acceptance model to assess the possibility of employees using MOOCs in corporate settings for reskilling and upskilling. The proposed model was formulated using the Technology Acceptance Model, Social Support Theory, and Theory of Belongingness as the foundations, besides extending the model with four additional constructs: perceived credibility, perceived convenience, digital competence, and perceived learning. Recommendations for conducting empirical research on the model are provided on how the model will be assessed to be successfully used in measuring employees’ acceptance of Corporate MOOCs.